Alternativas para o aumento da eficácia do processo de capacitação de novos funcionários de uma instituição bancária - Pravitz, Francine Barbosa (Universidade do Vale do Rio dos Sinos, 2024)
In a constantly evolving world, the need for effective training and development programs has never been more urgent. The landscape of banking institutions in Brazil reveals a robust and ever-transforming sector, playing a crucial role in the national economy. The intense competition and diversity among financial institutions drive an incessant quest for innovation and efficiency, highlighting the necessity for ongoing qualification and improvement of employees. This study aims to propose alternatives to enhance the effectiveness of the training process for new employees at the banking institution under study. Based on this, qualitative research of an exploratory nature will be carried out, operationalized by means in-depth individual interviews with a semi-structured approach, with management professionals, operational area employees and of the Institution’s Human Resources Sector. Data analysis will be carried out based on content analysis. The research reveals that the effectiveness of a training program is directly linked to the learning profile of each new employee. Additionally, it emphasizes the need for continuous revisions to the program to achieve the desired outcomes. Finally, the study points out that the lack of clarity and the absence of standardization in activities can compromise the success of training programs.
Keywords: Capacitação de funcionários; Qualidade no atendimento aos clientes; Operações em serviços; Desempenho profissional; Serviços financeiros; Employee training; Quality in customer service; Service operations; Professional performance; Financial services; ACCNPQ::Engenharias::Engenharia de Produção